Which institutions encourage entrepreneurs to create larger firms? - Saul Estrin; Julia Korosteleva; Tomasz Mickiewicz (Institute for the Study of Labor (IZA), 2011)
We develop entrepreneurship and institutional theory to explain variation in different types of entrepreneurship across individuals and institutional contexts. Our framework generates hypotheses about the negative impact of higher levels of corruption, weaker property rights and especially intellectual property rights, and a larger state on entrepreneurs who plan to grow faster. We test these hypotheses using the Global Entrepreneurship Monitor surveys in 55 countries for 2001-2006, applying a multilevel estimation framework. We confirm our main hypotheses but we find no significant impact from intellectual property rights.
urn:nbn:de:101:1-201104113544
Keywords: L26; D23; D84; J24; P11; 330; entrepreneurship; institutions; corruption; property rights; government; Global Entrepreneurship Monitor; Unternehmer; Unternehmensgründung; Institutionelle Infrastruktur; Korruption; Immaterialgüterrechte; Welt